Menelisik Inti Sari Petunjuk pada Sistematika Ayat dan Surat Al-Qur’an - bt Abdul Rahman, Waheeda; Muhtolib, Muhtolib (STAINI Press, 2024)
There have been quite a lot of studies of the Ulum al-Qur'an by commentators. The study pattern revolves around sciences related to the Koran and Tafsir. The aim of writing this article is to describe and examine the essence of the instructions in each verse in the systematics of verses and letters of the Koran. The method used in this research is the library research method. The approach used is a descriptive analysis approach, which is an approach used to collect data and information with various materials found in the library, such as books and articles. The results of his findings show that the Al-Qur'an has provided a very amazing uniqueness in terms of its verses and letters, as well as being a topic that is the focus of all Ulama and Mufasir, both classical and contemporary. The Ulama argue that the composition of the verses and letters of the Al-Qur'an based on the guidance of the Prophet Muhammad SAW which is tauqifi, thus forming a strong and sturdy order and sequence. This certainly indicates that there is a close connection between one verse and another. When observed and researched, a collection of verses from the Qur'an shows the meaning and secrets behind their composition. The scholars have several interesting opinions when explaining the relationship between verses and letters, so that it can be seen from several interpretations that the essence of each verse will emerge. Quran verses